WHISPERS OF LOSS: FILIPINO MOTHERS' UNTOLD JOURNEYS THROUGH INFANT GRIEF - Jason R. Lim, Jeanette P. Lim, Jonah M. Novo (Chelonian Research Foundation, 2024)
The study focused on the Lived experiences of Filipino bereaved mothers after infant deaths. The study made use of phenomenological research design. Moreover, a purposive sampling strategy was utilized to select participants who have experienced the loss of an infant within the past three years. Likewise, Data was collected through semi-structured interviews, which offered the flexibility to explore various aspects of the participants' experiences while ensuring consistency across interviews. Furthermore, the study yielded six themes: (1) Illusion of Normalcy, (2) Fierce Storm Within, (3) Seeking Meaning Amidst Sorrow, (4) The Weight of Shadows, (5) Finding Harmony in Chaos and (6) Finding Light in the Darkness. Moreover, The study highlights the struggle between societal expectations and inner turmoil faced by bereaved mothers, emphasizing the importance of personalized assistance and empathy. It highlights the need for a more comprehensive approach to addressing loss and trauma in mothers, as societal norms often overlook their emotions and difficulties.